Study of e+e-→pp[bar] via initial-state radiation at BABAR - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
The process e+e−→p¯pγ is studied using 469 fb−1 of integrated luminosity collected with the BABAR detector at the SLAC National Accelerator Laboratory, at an e+e− center-of-mass energy of 10.6 GeV. From the analysis of the p¯p invariant mass spectrum, the energy dependence of the cross section for e+e−→p¯p is measured from threshold to 4.5 GeV. The energy dependence of the ratio of electric and magnetic form factors, |GE/GM|, and the asymmetry in the proton angular distribution are measured for p¯p masses below 3 GeV. The branching fractions for the decays J/ψ→p¯p and ψ(2S)→p¯p are also determined.